Network for Early Onset Cystic Kidney Diseases—A Comprehensive Multidisciplinary Approach to Hereditary Cystic Kidney Diseases in Childhood - König, Jens Christian; Titieni, Andrea; Konrad, Martin; , The NEOCYST Consortium; Bergmann, C.; Cetiner, M.; Drube, J.; Gimpel, C.; Göbel, J.; Haffner, D.; Illig, T.; Klopp, N.; et al. (Frontiers in Pediatrics, 2018)
Hereditary cystic kidney diseases comprise a complex group of genetic disorders representing one of the most common causes of chronic renal failure in childhood. The main representatives are autosomal recessive polycystic kidney disease (ARPKD), nephronophthisis (NPH), Bardet-Biedl syndrome (BBS), and HNF1B nephropathy. Within the last years, genetic efforts have brought tremendous progress for the molecular understanding of hereditary cystic kidney diseases identifying more than 70 genes. Yet, genetic heterogeneity, phenotypic variability, a lack of reliable genotype-phenotype correlations and the absence of disease-specific biomarkers remain major challenges for physicians treating children with cystic kidney diseases. To tackle these challenges comprehensive scientific approaches are urgently needed that match the ongoing “revolution” in genetics and molecular biology with an improved efficacy of clinical data collection. NEOCYST (Network for Early Onset Cystic Kidney Diseases) is a multidisciplinary, multicenter collaborative combining a detailed collection of clinical data with translational scientific approaches addressing the genetic, molecular and functional background of hereditary cystic kidney diseases. Consisting of seven work packages including an international registry as well as a biobank, NEOCYST is not only dedicated to current scientific questions but also provides a platform for longitudinal clinical surveillance and supplies precious sources for high-quality research projects and future clinical trials. Funded by the German Federal Government (BMBF), the NEOCYST collaborative started in February 2016. Here we would like to introduce the rationale, design and objectives of the network followed by a short overview on the current state of progress.